“Je est un autre” : Maupassant et l’angoissante altérité du Moi - Carvalho, Ana Alexandra Seabra de (2022)
Maupassant dissects, from a pessimistic perspective, the social and human universe of his time, describing both Parisian life and that of Normandy. Author of several novels, he is truly a master of short stories. His aesthetic seeks efficiency, valuing the power of image, sobriety and rigor of expression. On the other hand, the writer also cultivates the fantastic genre, providing it with innovative elements such as the internalization of strange phenomena, based on the disorder of reason, inner anguish, imaginary and obsessive fears, questioning mankind about its own identity. For this disciple of Flaubert, the real world (both nature and society) is in its essence bad and absurd. So, his fantastic stories are marked by the sobriety of processes and elements; they immerse us, however, in the universe of anxious fear that comes from within. Above all, there is the fear of the invisible, the phobia of madness and the attraction of suicide as the ultimate salvation. We’ll revisit six Maupassant’s short stories (Sur l’eau, Lui?, Un fou?, Lettre d’un fou, Le Horla, and Qui sait?) where everyday life appears so frightening by its strangeness and cruelty and the theme of the Doppelgänger is developed.